KINERJA PENYULUH PERTANIAN DALAM MENINGKATKAN PRODUKSI TANAMAN PADI DI KECAMATAN BANGKINANG KABUPATEN KAMPAR - Perdana S., Jophy; Sahuri, Chalid (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2016)
Guidance given by the Agricultural extension officers in district Bangkinang to farmers must comply with the general principle of extension so that it can give good service. The performance of the Agricultural extension officers in increasing the production of rice plant results in district Bangkinang can be said either because the agricultural extension officers in the porch of the Bangkinang Sub-district agricultural extension has provided guidance in accordance with the principle of the extension so that it can assist and improve the production results of the farmers. Facilities owned by the Sub-district agricultural extension Bangkinang Hall is indeed not enough adequate but the agricultural extension officers possesses the ability of considerable quality. Agricultural extension officers give their time to do outreach with supervision and routine monitoring with farmers and farmer groups. Then the agricultural extension officers are always friendly and polite in doing outreach. The purpose of this research is to analyze the performance of the agricultural extension officers in increasing the production of rice plant in the subdistrict of Kampar Regency Bangkinang and aware of the factors that affected it.This research uses theories of umar where performance is determined by the indicator of reliability, initiative, presence, quality of the work. This research uses qualitative, descriptive methods, techniques of collecting data through observation and interviews where the parties involved in this study as an informant.The results of this research show that extension officers in Pertanain Sub-district agricultural extension Bangkinang Hall has good performance in doing outreach to farmers and in accordance with the expectations and the needs of farmers. Starting from the reliability of the farmers who believe in by farmers, extension officers initiative in resolving the problem, often visiting the farmers into the field, the quality of a good job and serve the community with a friendly attitude. Factors â factors that affect the performance of the agriculturalextension officers in increasing the production of rice plant in the subdistrict of Kampar Regency Bangkinang is infrastructure, work environment, work and passions.Keywords : performance, agricultural extension officers, the production of riceplant